2017
DOI: 10.3390/ma10091059
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Nano- and Microcrystals of EuPO4 Created by One-Step Synthesis of Antimony-Germanate-Silicate Glass Modified by P2O5

Abstract: Abstract:Technology of active glass-ceramics (GC) is an important part of luminescent materials engineering. The classic method to obtain GC is based on annealing of parent glass in proper temperature and different time periods. Generally, only the bulk materials are investigated as a starting host for further applications. However, the effect of an additional heat-treatment process on emission and structural properties during GC processing is omitted. Here, we focus on the possibility of obtaining transparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Based on these changes, the asymmetric ratio (AR) intensities, defined as the relation of the electric dipole transition ( 5 D 0 → 7 F 2 ) to the magnetic dipole transition ( 5 D 0 → 7 F 1 ), were estimated (inset in Figure 8). The value of the ( 5 D 0 → 7 F 2 )/( 5 D 0 → 7 F 1 ) transition ratio gives a factor of the degree of structural distortion from the inversion symmetry of the local environment of the europium ions [39]. We observed that replacing the BaO by P 2 O 5 up to 20 mol.% leads to a decrease of the asymmetric ratio, which is related to the partial structural arrangement in the ligand field around Eu 3+ ions.…”
Section: Photoluminescence Excitation Emission Spectra and Luminescence Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these changes, the asymmetric ratio (AR) intensities, defined as the relation of the electric dipole transition ( 5 D 0 → 7 F 2 ) to the magnetic dipole transition ( 5 D 0 → 7 F 1 ), were estimated (inset in Figure 8). The value of the ( 5 D 0 → 7 F 2 )/( 5 D 0 → 7 F 1 ) transition ratio gives a factor of the degree of structural distortion from the inversion symmetry of the local environment of the europium ions [39]. We observed that replacing the BaO by P 2 O 5 up to 20 mol.% leads to a decrease of the asymmetric ratio, which is related to the partial structural arrangement in the ligand field around Eu 3+ ions.…”
Section: Photoluminescence Excitation Emission Spectra and Luminescence Kineticsmentioning
confidence: 99%
“…The phosphorous oxide is characterized by high phonon energy (1200 cm −1 ) and reduces clustering effects via non-bridging oxygen formation, better incorporating rare earth ions promoting more efficient emissions than pure germanate glasses [37]. Even more interesting is that the P 2 O 5 can be used as a nucleating agent for transparent glass-ceramic materials [38,39]. In view of the above, it is important to find a suitable composition of germanate glass that might be potentially used to produce the glass-ceramic material with functionalized luminescent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our earlier investigations, SGS glass was chosen for this investigation because of its good thermal stability, and low phonon energy glass matrix, which can improve quantum efficiency and probability of radiative transitions for electrons of rare-earth ion dopant [ 4 , 6 , 30 ]. Another reason was the possibility of shaping SGS into optic fibers.…”
Section: Introductionmentioning
confidence: 99%
“…This research analyzed the effect of P 2 O 5 concentration on the luminescence spectra, asymmetry ratio (AR), and luminescence decay. Due to earlier work [ 30 ], we decided to limit the P 2 O 5 concentration up to 1 mol%, and we mainly focused on investigating the crystallization process in antimony-germanate-silicate glass, enabling size and density control of EuPO 4 nanocrystals. The main objective of this experiment was to obtain a good optical quality core material as an 11 mm dia rod with specific crystalline properties and crystallization conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the Eu 3+ ion is also its common use as a spectroscopic probe of the site symmetry in different host matrices [9,10]. The main approach relies on the analysis of the intensity ratio of electrical-dipole (ED: 5 D 0 → 7 F 2 ) to magnetic-dipole (MD: 5 D 0 → 7 F 1 ) transitions, which determines the asymmetry of the ligand environment and the covalency of metal-ligand bond [11,12].…”
Section: Introductionmentioning
confidence: 99%